Environmental & architectural phenomenology. Vol. 31, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2020)
Besides “items of interest,” and “citations received,” this issue includes the following items: An “in memoriam” for architectural theorist Bill Hillier, who died in November; Entries relating to Goethean science as a phenomenology of nature, including three “book notes” on recently-published volumes as well as the last part of philosopher Henri Bortoft’s essay, “Goethean Science and the Wholeness of Nature;” A “book note” on sociologist Michael Hviid Jacobsen’s Encountering the Everyday: An Introduction to the Sociology of the Unnoticed; Essays by writer David Ferlic (“Walking the Dog Phenomenologically”) and anthropologist Kevin Browne (“Negotiating National Memory and Forgetting through Cemeteries”); Psychologist Akihiro Yoshida’s Japanese translation of the “twenty-three definitions of phenomenology,” originally published in the 2019 summer/fall issue of EAP.
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals